2004
DOI: 10.1111/j.1365-2745.2004.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predisposing episodic drought‐induced tree mortality in Nothofagus– site, climatic sensitivity and growth trends

Abstract: Summary 1Although climatic variability is a strong driving force for forest dynamics, drought-induced mortality has generally received much less attention than other types of disturbance. 2 In 1998-99 northern Patagonia was affected by one of the most severe droughts of the 20th century, coinciding with a strong La Nina event, and this caused high mortality of Nothofagus dombeyi (coihue), the dominant tree species in Nahuel Huapi National Park. 3 Factors involved in determining this mortality of N. dombeyi wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
248
5
18

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(282 citation statements)
references
References 47 publications
11
248
5
18
Order By: Relevance
“…The interpretation of this higher sensitivity from the viewpoint of the ability of cedar to cope with drought effects is not straightforward, and we still lack a conceptual framework linking the growth signal features to life traits (Cuny et al 2012) and demography (Martínez-Vilalta et al 2012). Indeed, previous studies produced seemingly contradictory results, reporting higher mortality rates for trees showing highly variable growth (Suarez and Ghermandi 2004) or a weaker correlation between the growth of the dying trees and the climate variables (Linares et al 2010). As recent reports suggest a lower capacity of large trees to overcome severe drought (Bigler and Veblen 2009), the long-term effect on thinning on the ability of mature cedar stands to survive extreme water stress events need further investigations.…”
Section: Management Perspectivesmentioning
confidence: 78%
“…The interpretation of this higher sensitivity from the viewpoint of the ability of cedar to cope with drought effects is not straightforward, and we still lack a conceptual framework linking the growth signal features to life traits (Cuny et al 2012) and demography (Martínez-Vilalta et al 2012). Indeed, previous studies produced seemingly contradictory results, reporting higher mortality rates for trees showing highly variable growth (Suarez and Ghermandi 2004) or a weaker correlation between the growth of the dying trees and the climate variables (Linares et al 2010). As recent reports suggest a lower capacity of large trees to overcome severe drought (Bigler and Veblen 2009), the long-term effect on thinning on the ability of mature cedar stands to survive extreme water stress events need further investigations.…”
Section: Management Perspectivesmentioning
confidence: 78%
“…Some additional stress factors like soil hydromorphy or nitrogen excess could also be involved in the process. A growing body of evidence in the literature supports the notion that the risk of tree death increases with a decreasing growth rate [107,140]. Wyckoff and Clark [155], using various growth-mortality functions, showed that dead trees of Cornus florida and Acer rubrum exhibited lower growth rates during the 5 years prior to mortality than surviving ones.…”
Section: Drought Induced Mortalitymentioning
confidence: 86%
“…This variable represents the responsiveness of individuals to environmental signals, such as climate (Fritts, 1976). High sensitivity values have been associated with tree vigour decline because dying trees may exhibit higher variability in past growth rates (Ogle et al, 2000;Suarez et al, 2004). Interannual sensitivity was defined as (Fritts, 1976):…”
Section: Logistic Regressionmentioning
confidence: 99%